Evaluasi Penerapan Metode PKM dalam Pendidikan K3 di PT. Kuala Pelabuhan Indonesia (KPI) Meningkatkan Kesadaran dan Keterampilan Pekerja untuk Mengurangi Risiko Kecelakaan - Habel Taime; Fransiska Datu (STIE Jambatan Bulan, 2024)
Occupational Health and Safety (OHS) is a crucial aspect in creating a safe and productive work environment at PT. Kuala Pelabuhan Indonesia (KPI) in Mimika Regency. This research aims to evaluate the OHS education pattern implemented at PT. KPI using the PKM (Skills and Management Approach) method to minimize unsafe behavior in the workplace. The PKM method involves practical training, demonstrations of safety equipment usage, emergency evacuation simulations, and periodic safety inspections. The results show that consistent application of the PKM method can enhance workers' awareness and skills in facing potential hazards, thereby reducing the risk of workplace accidents. Structured training focusing on practical skills and good safety management has proven effective in fostering a safety culture in the workplace. Thus, the implementation of OHS education using the PKM method at PT. KPI is expected to serve as a model for other companies to improve overall occupational health and safety..